Planning analysis of solar power plant utilization using the PLN network grid system interconnection on Samudra University roof building - ferri Festika; Ahmad Syuhada; Hamdani Umar (Jurnal POLIMESIN, 2023)
Solar power plants can be applied in various forms of installation, either centralised or distributed, with each configuration system installation being either on-grid or off-grid. Samudra University plans to install a solar power plant for environmentally friendly applications and energy savings. The purpose of this study is to investigate the feasibility and benefits of Samudra University installing solar power generation capacity using a single-owner system on campus using SAM (System Advisor Model) applications using two axes with PV energy. The method used is to model the photovoltaic results with the System Advisor Model (SAM), which can develop new renewable energy photovoltaics. The use of solar energy as a producer of electrical energy in buildings at the ocean university by using the System Advisor Model application on the Single Owner (Grid) system in collaboration with local electricity (PLN) to continue the energy needs produced as much as 32,652,394 kWh will cost Rp. 372,864,450,000, and with an area of 105,179.9 m2 or ± 11 hectares of the total area of 49.8 hectares, it only uses ± 20% of the total area